Featured Cover. Issue 8 (12th July 2021) - Mortensen, Ninell P.; Moreno Caffaro, Maria; Patel, Purvi R.; Snyder, Rodney W.; Watson, Scott L.; Aravamudhan, Shyam; Montgomery, Stephanie A.; Lefever, Timothy; Sumner, Susan J.; Fennell, Timothy R.
Abstract : The cover image is based on the Research Article Biodistribution, cardiac and neurobehavioral assessments, and neurotransmitter quantification in juvenile rats following oral administration of aluminum oxide nanoparticles by Ninell P. Mortensen et al., https://doi.org/10.1002/jat.4122 .